(untitled) (Jurnal iSpectrum, 2023)
Mental health is something that people rarely pay attention to nowadays. Especially early childhood mental health which is very common, because this is very influential when these children grow up. Some of the influencing factors include, children are addicted to playing gadgets/games, children have emotional problems or tantrums, lack of quality time or lack of closeness between parents and children. Most of this happens because in urban areas, especially Denpasar, parents are busy with their work or business. Therefore, not a few parents do not know the interests and talents of their own children and tend to be forced to follow their parents’ wishes. Apart from environmental factors, children can also experience problems from themselves, for example delays in talking, walking, and tantrums. This is a problem that must be resolved because it also concerns the future of the child. Child counseling services are also rarely known by parents out there, and also in Bali children’s consultations are usually combined with psychology clinics for adults and adolescents, and of course in terms of child-friendly facilities it can be said to be inadequate. Like there is no special room for interest and aptitude tests, IQ and preschool tests, playground room, vocal and music room, seminar room for parents about parenting science, and other rooms.